2015
DOI: 10.1016/j.bbr.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of observers on behavior and the brain during aggressive encounters

Abstract: What effect does an audience have on an animal’s behavior and where is this influence registered in the brain? To answer these questions, we analyzed male cichlid fish fighting in the presence of audiences of various compositions and measured expression of immediate early genes in the brain as a proxy for neural activity. We hypothesized their behavior would change depending on who was watching them. We measured behavioral responses from both the “watchers” and the “watched” during aggressive encounters and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This is important because extensive studies have shown that the expression of the immediate early gene Egr‐1, which has been linked to long‐term social memory in Apteronotus (Harvey‐Girard et al, 2011), is highly conserved in this species (Burmeister et al, ). Fernald and colleagues have shown that social interactions can induce Egr‐1 expression in various brain regions, including DL and DM (Burmeister et al, ; Maruska et al, ; Desjardins et al, ). These studies were done using microdissected brain regions and did not evaluate Egr‐1 mRNA expression in DC2 (DD?).…”
Section: Discussionmentioning
confidence: 99%
“…This is important because extensive studies have shown that the expression of the immediate early gene Egr‐1, which has been linked to long‐term social memory in Apteronotus (Harvey‐Girard et al, 2011), is highly conserved in this species (Burmeister et al, ). Fernald and colleagues have shown that social interactions can induce Egr‐1 expression in various brain regions, including DL and DM (Burmeister et al, ; Maruska et al, ; Desjardins et al, ). These studies were done using microdissected brain regions and did not evaluate Egr‐1 mRNA expression in DC2 (DD?).…”
Section: Discussionmentioning
confidence: 99%
“…Not only will this vastly expand the number of candidate species, but it will also facilitate studies into patterns of neural activity in response to social stimuli through quantiଏcation of immediate early gene (IEG) expression levels (e.g. transcription factors c-Fos, EGR-1) in candidate regions of the SDMN using similar approaches to numerous neuroethological studies involving ଏshes (Desjardins et al 2015;Maruska et al 2013;Roleira et al 2017;Teles et al 2015Teles et al , 2016Weitekamp and Hofmann 2017). Cichlids are also amenable to CRISPR gene editing and other genetic tools that allow selective manipulation of candidate neural circuits involved in social interactions (Juntti 2019), providing experimental potential to examine candidate mechanistic pathways underlying social behaviour.…”
Section: The (Co-)evolution Of Social Structure and Behaviourmentioning
confidence: 99%
“…In a mate choice paradigm, Astatotilapia burtoni females showed a different pattern of activation of SDMN nodes after watching their preferred mate either winning or losing an agonistic interaction: SDMN nodes related to reproduction (i.e., pre-optic area and fish homolog of the ventromedial hypothalamus) were activated when their preferred mate won the fight, whereas nodes linked to anxiety (i.e., fish homolog of the lateral septum) were more active when their preferred mate lost the fight (Desjardins et al, 2010 ). In another study, relative body size has also been shown to influence the pattern of activation of SDMN nuclei, with larger body size inducing a higher activation of brain regions related to anxiety, both in fighting fish perceiving a audience made up of larger fish, or in eavesdroppers attending a fight between larger individuals (Desjardins et al, 2015 ). Finally, in zebrafish the brain transcriptomic changes associated with social eavesdropping have been shown to comprise an up-regulation of genes related to alertness and memory formation in fish eavesdropping a fight between conspecifics (Lopes et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%